A Coordinated Suite of Wild-Introgression Lines in Indica and Japonica Elite Backgrounds - Singh, Namrata; Wang, Diane R.; Ali, Liakat; Kim, HyunJung; Akther, Kazi M.; Harrington, Sandra E.; Kang, Ju-Won; Shakiba, Ehsan; Shi, Yuxin; DeClerck, Genevieve; Meadows, Byron; Govindaraj, Vishnu; et al. (Frontiers in Plant Science, 2020)
Rice, Oryza sativa L., is a cultivated, inbreeding species that serves as the staple food for the largest number of people on earth. It has two strongly diverged varietal groups, Indica and Japonica, which result from a combination of natural and human selection. The genetic divergence of these groups reflects the underlying population structure of their wild ancestors, and suggests that a pre-breeding strategy designed to take advantage of existing genetic, geographic and ecological substructure may provide a rational approach to the utilization of crop wild ancestors in plant improvement. Here we describe the coordinated development of six introgression libraries (n = 63 to 81 lines per library) in both Indica (cv. IR64) and Japonica (cv. Cybonnet) backgrounds using three bio-geographically diverse wild donors representing the Oryza rufipogon Species Complex from China, Laos and Indonesia. The final libraries were genotyped using an Infinium 7K rice SNP array (C7AIR) and analyzed under greenhouse conditions for several simply inherited (Mendelian) traits. These six interspecific populations can be used as individual Chromosome Segment Substitution Line libraries and, when considered together, serve as a powerful genetic resource for systematic genetic dissection of agronomic, physiological and developmental traits in rice.